Review Kebutuhan Teknisi Pesawat Terbang Bersertifikat di Industri MRO Indonesia, Permasalahan dan Strategi Pemenuhannya - Freddy Franciscus (FTK UNSURYA, 2019)
Jumlah pesawat terbang di Indonesia tumbuh 14,5% per tahun demikian juga dengan MRO market. Sejalan dengan hal tersebut dibutuhkan tambahan teknisi pesawat terbang ber sertifikat yaitu sekitar 800-1000 teknisi per tahun sampai dengan 5 tahun ke depan. Pada Tahun 2018 kebutuhan teknisi bersertifikat tersebut dapat di supply hanya sekitar 448 teknisi oleh beberapa Sekolah Aircraft Maintenance Training Organization AMTO/Perguruan Tinggi/Politeknik seperti antara lain STPI, Universitas Suryadarma, Politeknik Batham dll. Terjadi kekurangan supply/’gap’ teknisi bersertifikat sekitar 350-550 teknisi. Kekurangan supply teknisi antara lain disebabkan oleh kurangnya peminat untuk jadi teknisi, cukup mahalnya sekolah AMTO, terbatasnya jumlah sekolah AMTO dan terbatasnya kapasitas daya tamping sekolah AMTO yang ada. Sementara ini penanggulangan ‘gap’ kekurangan teknisi adalah dengan memperpanjang teknisi yang sudah purna bakti. Beberapa strategi jangka Panjang mengatasi permasalahan kekurangan teknisi antara lain meningkatkan kerjasama antara MRO dengan Airlines, Kementrian terkait dan Institusi Pendidikan untuk melakukan promosi tentang peran penting teknisi AMTO, mengusahakan beasiswa/subsidi, menambah jumlah sekolah AMTO dan melakukan penambahan instruktur/dosen bersertifikat lewat program Basic Aircraft Maintenance/BAM dosen. The number of airplanes in Indonesia grew 14.5% per year as well as the MRO market. In line with this, additional aircraft certified technicians are required around 800-1000 technicians per year for the next 5 years. In 2018 the needs of certified technicians could be supplied only around 448 technicians by several AMTO School of Aircraft Maintenance Training Organizations AMTO/ Colleges / Polytechnics such as STPI, Suryadarma University, Batham Polytechnic etc. There is a shortage of supply / 'gap' certified technicians around 350-550 technicians. The shortage of technician supplies was partly due to a lack of interest to become technicians, quite expensive AMTO schools, the limited number of AMTO schools and the limited capacity of existing AMTO schools. While this gap countermeasure for technicians shortcomings is to extend senior technicians who have been retired. Some strategies to overcome the problem of lack of technicians are increasing collaboration between MRO and Airlines, related Ministry and Educational Institutions to promote the important role of AMTO technicians, seeking scholarships / subsidies, increasing the number of AMTO schools and adding certified instructors / lecturers through the Basic Aircraft Maintenance BAM program.